Современные возможности лапароскопической пластики мочепузырно-прямокишечного свища - A. I. Tkachenko; D. N. Osadchii; V. V. Lysenko; V. E. Maksimovskii; O. V. Lukianchuk; S. G. Chetverikov; V. V. Lysachenko; A. M. Chaika; R. S. Chistiakov; A. D. Melenevskii; A. A. Mashukov; D. V. Atanasov; et al. (Клінічна хірургія)
Современные возможности лапароскопической пластики мочепузырно-прямокишечного свища